Three-dimensional radiotherapy planning in the pelvic region of wild animals - Silva, Diego Andrade; Vettorato, Michel de Campos; Rahal, Sheila Canevese; Fernandes, Marco Antônio Rodrigues (Archives of Veterinary Science, 2021)
Radiotherapy is a medical modality that has been constantly revolutionizing with the offer of three-dimensional computational for treatment planning systems (TPS), providing greater security in the release of the radiation dose in the target volume, improving the therapeutic response and minimizing the radiobiological effects unwanted. The incorporation of modern radiotherapy techniques, along with studies that contribute to the development of radiotherapy protocols in veterinary medicine, may contribute to improve the quality of treatments and survival of animals affected by cancer. A TPS applied in a human radiotherapy clinic was used and the radiometric, clinical and anatomical parameters were adequate for the feasibility of use in veterinary radiotherapy. Tomographic images of the pelvic region of wild animals assisted by the School of Veterinary Medicine and Animal Science (FMVZ/UNESP) were used to perform them. Protocols for the implementation of computational planning in veterinary medicine were verified by analyzing the homogeneity of the radiation dose distribution in the planned treatment volume (PTV) and ensuring the protection of the organs surrounding the PTV. The methodology applied for the use of TPS Eclipse in veterinary radiotherapy planning proved to be feasible, and can present itself as an important tool to improve veterinary oncological therapeutic approaches.